2018
DOI: 10.1155/2018/7458361
|View full text |Cite
|
Sign up to set email alerts
|

Area of Residence and Socioeconomic Factors Reduce Access to Biologics for Rheumatoid Arthritis Patients in Romania

Abstract: Introduction The study aimed to evaluate the influence of socioeconomic factors on rheumatoid arthritis (RA) patients' access to biologics in Romania. Method Cross-sectional data were collected in January 2014 from the Romanian Registry of Rheumatic Diseases (RRRD) comprising all RA patients on biologics from 42 Romanian counties. “Territorial” access to biologics was defined by patients receiving biologics in their home county. A county was “equitable” if <25% of RA patients received biologics outside it. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Other factors such as the area of residence and low education class negatively impacted access to biologic agents. Moreover, elderly patients had less access to these drugs in other studies [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as the area of residence and low education class negatively impacted access to biologic agents. Moreover, elderly patients had less access to these drugs in other studies [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the present study, the frequency of adherent patients was comparable and rural residence was among the most important factors associated with non-adherence to medications in Egyptian RA cases [ 4 ]. Similarly, in Romania, urban RA patients had a significantly higher frequency of biologic access than those from rural areas [ 35 ]. Rural clinic location was associated with lower use of biologics suggesting a possible prescription bias or patient preferences due to convenience [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that this warranted further investigation as, despite universal access to treatment in Sweden, different counties seemed to have different initiation thresholds, perhaps reflecting different treatment traditions among rheumatologists as well as county-specific economic considerations. Regional differences were also found in Romania, where urban dwellers and those living in regions with higher living standards were more likely to receive biologics than those living in more deprived areas (Codreanu et al, 2018). This is unlikely to be accounted for by differences in patient incomes, as co-payments for biologics are not required in Romania (Kawalec et al, 2017).…”
Section: Rheumatoid Arthritismentioning
confidence: 96%